The metonymic mechanism of English translation of Chinese intangible cultural heritage terms from the perspective of cognitive psychology - Jiang, Liping; Al-Shaibani, Ghayth K. Sh.; Yang, Fenglin; Cheng, Mengmeng; Huang, Minghuan (Frontiers in Psychology, 2022)
Intangible Cultural Heritage terms are heavily loaded with specific historical and cultural knowledge and regional characteristics. Based on the cognitive psychology, this paper analyzes the metonymic mechanism of traditional translation techniques such as substitution in the English translation of intangible cultural heritage terms. The English translation of Intangible Cultural Heritage nominal terms can be realized based on the metonymic mechanism of replacing the whole with part or part with part of the linguistic structure. The English translation of Intangible Cultural Heritage verbal terms can regard the whole verbal action as an event process and highlight one aspect of the process through metonymic mechanism. This paper holds that metonymy is an important psychological motivation and cognitive mechanism behind translation skills such as substitution, and brings the relationship between the corresponding items of the target language and the source language into a unified interpretation framework, which has certain guiding significance for the research of translation theory and translation practice.